Legal Protection for the Use of Copyright of Songs and/or Music in Live Streaming Concerts Through Digital Platforms in Indonesia - Diana Silfiani (Faculty of Law, Universitas Padjadjaran, 2022)
The Covid-19 pandemic has accelerated the digital influence on the Indonesian music industry. Music concerts, which are usually held offline with crowds of people, are no longer possible because crowds can make new clusters of Covid-19. The Indonesian music industry needs alternatives to survive the pandemic, and the advance in technology has the solution. Virtual concerts that are broadcasted via digital platforms have started to thrive. They use copyrighted songs and/or music so that royalty payments are made in accordance with the type of use and needs. Unfortunately, the Law Number 28 of 2014 on Copyright and the Government Regulation Number 56 of 2021 on the Management of Song and/or Music Copyright Royalties do not regulate the use in detail and specific manners. Therefore, the industry actors have not found the right payment formula for the economic rights royalties. The absence of regulations certainly does not reduce the user’s primary obligation to obtain a songwriter's permission and pay royalties for song and/or music copyrights. The fulfillment of the obligation to pay royalties must still be accomplished with due regard to applicable provisions. This study examined the problems with a normative juridical method. It considered the practices and customs that apply in Indonesia. It also generated some perspectives from relevant stakeholders. DOI: https://doi.org/10.22304/pjih.v9n2.a1